Quasi-stiffness of the knee joint in flexion and extension during the golf swing - Choi, A.; Sim, T.; Mun, J. H. (Journal of Sports Sciences, 2015)
Biomechanical understanding of the knee joint during a golf swing is essential to improve performance and prevent injury. In this study, we quantified the flexion/extension angle and moment as the primary knee movement, and evaluated quasi-stiffness represented by moment-angle coupling in the knee joint. Eighteen skilled and 23 unskilled golfers participated in this study. Six infrared cameras and two force platforms were used to record a swing motion. The anatomical angle and moment were calculated from kinematic and kinetic models, and quasi-stiffness of the knee joint was determined as an instantaneous slope of moment-angle curves. The lead knee of the skilled group had decreased resistance duration compared with the unskilled group (P < 0.05), and the resistance duration of the lead knee was lower than that of the trail knee in the skilled group (P < 0.01). The lead knee of the skilled golfers had greater flexible excursion duration than the trail knee of the skilled golfers, and of both the lead and trail knees of the unskilled golfers. These results provide critical information for preventing knee injuries during a golf swing and developing rehabilitation strategies following surgery.